(untitled) (Bangladesh Journal of Agricultural Research, 2011)
Field experiments were conducted through T. Aman 2003–Boro 2008 at the Bangladesh Rice Research Institute (BRRI), Gazipur Farm with a view to determining the appropriate dose of K fertilizer in soils under double rice cropping system and to find out the alternative source of K for wet land rice cultivation. Four levels of inorganic K (0, 33, 50 & 66 kg K/ha and farmers’ practice from MoP) and one recycling of rice straw 4.5 t/ha (dry basis) were tested. Incorporation of rice straw into soil contributed significantly to grain yield in successive growing seasons comparable with inorganic K fertilizer. In clay- loam soil, K at the rate of 50 kg K/ha should be applied to obtain the maximum yield in both T. Aman and Boro rice seasons. Rice straw may be a potential alternative source of K for sustaining soil K fertility and maximizing rice yield. Agronomic use efficiency of K decreased with increasing K levels. A narrower balance of K was observed when rice straw or a higher dose of inorganic K fertilizer was used. Keywords: K; rice yield; soil K balance; rice straw. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9258 BJAR 2011; 36(2): 305-311